CD133/prominin1 is prognostic for GBM patient's survival, but inversely correlated with cysteine cathepsine' expression in gliobastoma derived spheroids - Ardebili, Seyed Yousef (Radiology and oncology (Ljubljana), 2011)
Introduction. CD133 is a marker for a population of glioblastoma (GBM) and normal neural stem cells (NNSC). We aimed to reveal whether the migratory potential and differentiation of these stem cells is associated with CD133 expression and with cathepsin proteases (Cats). Materials and methods. The invasiveness of normal NNSC, GBM/CD133+ cell lines and GBM spheroids was evaluated in 3D collagen, as well as of U87-MG and normal astrocytes (NHA) grown in monolayers in 2D Matrigel. Expression of Cats B, L and S was measuredat mRNA and activity levels and their relation to invasiveness, to CD133 mRNA in 26 gliomas, and to the survival of these patients. Results. The average yield of CD133+ cells from GBM samples was 9.6%. Survival of patients with higher CD133 mRNA expression was significantly shorter (p< 0.005). Invasion, associated with proteolytic degradation of matrix, was higher in normal stem cells and GBM spheroids and cells than in isolated GBM CD133+ cells. In glioma samples, there was no correlation between CD133 mRNA expression and Cat mRNAs, but there was an inverse correlation with Cat activities. Conclusions. The study confirms CD133 as a prognostic marker for the survival of GBM patients. We demonstrated that NNSC have higher invasion potential and invade the collagen matrix in a mode different from that of GBM,initiating stem cell spheres. This result could have implications for the design of new therapeutics, including protease inhibitors that specifically target invasive tumour stem cells. Increased activity of cathepsins in CD133- cells suggests their role in the invasive behaviour of GBM.
Keywords: diagnostika; glioblasom; označevalci; prognoza; tumorske celice